HPLC-DAD Determination of Nitrite and Nitrate in Human Saliva Utilizing a Phosphatidylcholine Column - Małgorzata Tatarczak-Michalewska; Jolanta Flieger; Justyna Kawka; Wojciech Płaziński; Wojciech Flieger; Eliza Blicharska; Dariusz Majerek (Molecules, 2019)
The aim of this research was to optimize the separation and quantitative determination of nitrites and nitrates in human saliva. HPLC with UV absorption (HPLC/DAD) using a phosphatidylcholine column (IAM.PC.DD2 Regis HPLC) was applied in this assay. Nitrates were detected directly by their absorbance at 210 nm, whereas nitrites were detected after oxidation to nitrates by potassium permanganate at acidic conditions. The kinetics of the permanganate−nitrite reaction was measured chromatographically. The calibration graph for nitrates was linear in the range of 0.5−35 µg mL−1 with a correlation coefficient of 0.9999. The limit of detection was 4.56 ng mL−1. The calibration graph for nitrites (after oxidation to nitrates) was linear in the range of 0.5−15 µg mL−1 with a correlation coefficient of 0.9972. The limit of detection was 4.21 ng mL−1. The nitrate concentrations in the saliva samples were found in the range of 8.98−18.52 μg mL−1, whereas nitrite was in the range of 3.50−5.34 μg mL−1.